Investigating dysregulated pathways in Staphylococcus aureus (SA) exposed macrophages based on pathway interaction network. (February 2017) - Zhou, Wei; Zhang, Yan; Li, Yue-Hua; Wang, Shuang; Zhang, Jing-Jing; Zhang, Cui-Xia; Zhang, Zhi-Sheng
Graphical abstract: Highlights: The PIN was comprised of 8388 interactions and 1189 nodes. Respiratory electron transport, ATP synthesis by chemiosmotic coupling, and heat production by uncoupling proteins was the seed pathway. A total of 15 dysregulated pathways were obtained for SA infected samples. Abstract: Objective: This work aimed to identify dysregulated pathways for Staphylococcus aureus (SA) exposed macrophages based on pathway interaction network (PIN). Methods: The inference of dysregulated pathways was comprised of four steps: preparing gene expression data, protein–protein interaction (PPI) data and pathway data; constructing a PIN dependent on the data and Pearson correlation coefficient (PCC); selecting seed pathway from PIN by computing activity score for each pathway according to principal component analysis (PCA) method; and investigating dysregulated pathways in a minimum set of pathways (MSP) utilizing seed pathway and the area under the receiver operating characteristics curve (AUC) index implemented in support vector machines (SVM) model. Results: A total of 20, 545 genes, 449, 833 interactions and 1189 pathways were obtained in the gene expression data, PPI data and pathway data, respectively. The PIN was consisted of 8388 interactions and 1189 nodes, and Respiratory electron transport, ATP synthesis by chemiosmotic coupling, and heat production by uncoupling proteins was identified as the seed pathway. Finally, 15 dysregulated pathways in MSP (AUC = 0.999) were obtained for SA infected samples, such as Respiratory electron transport and DNA Replication. Conclusions: We have identified 15 dysregulated pathways for SA infected macrophages based on PIN. The findings might provide potential biomarkers for early detection and therapy of SA infection, and give insights to reveal the molecular mechanism underlying SA infections. However, how these dysregulated pathways worked together still needs to be studied.